Mastery of non-mastery in the age of meltdown - Taussig, Michael T. 1940- (University of Chicago Press, 2020)
Smoke and Mirrors -- Mimetic excess -- The exposition of the non-dogmatic cannot be dogmatic -- Nietzsche's tuning fork, Kafka's sirens -- Twilight of the idols -- Catastrophe : the solar inversion of satanic denial -- Metamorphic sublimity -- Re-enchantment of nature -- In your bones you know otherwise -- Planetarium -- Sunset -- In the beginning Was the firefly -- The sun Is an Indian shaman -- Lightning -- Is magic domination of nature? -- The alpha and omega of all mastery -- Art versus art -- Subterranean cities of sleep -- Magic hour -- Julio Reyes's phantom ship
Includes bibliographical references and index
Keywords: Anpassung; Humanökologie; Anthropozän; Human ecology / Philosophy; Nature and civilization; Civilization, Modern / 21st century; Human ecology in art